FAKTOR-FAKTOR MEMPENGARUHI HARGA SAHAM TERHADAP PERUSAHAAN TRANSPORTASI DAN LOGISTIK BURSA EFEK INDONESIA - Eky Kriswahyuni; Syahril Effendi (JURNAL AKUNTANSI BARELANG, 2021)
Transportation and logistics companies are sectors of companies that are affected by the presence of Covid-19.The purpose of this study was to determine the ratio of financial analysis with liquidity, activity, profitability and solvency partially and simultaneously on stock prices in the transportation and logistics sectors. The method used in this research is secondary data analysis of the financial statements of transportation and logistics companies listed on the IDX from 2015-2019 which are quantitative with a population of 60, the number of samples is 11 using non-probability purposive sampling type so that 55 data reports finance. The results of the study partially show that the liquidity value has no effect on stock prices, activity affects stock prices with a value of, profitability affects stock prices with a value of, solvency has no effect on stock prices with a value of. Simultaneously (simultaneously) Liquidity, Activity, Profitability, Solvency on share prices.